SPECIFIC ASPECTS OF PROVE IN CONFISCATION OF PROPERTY (Conferencea, 2024)
This article analyzes the specific aspects of evidence collection and evaluation during property confiscation. At the same time, this article analyzes the norms of confiscation of property in international documents.